QUASICOHERENT PULSED RADAR SIGNAL PROCESSING - Прокопенко, І. Г.; Омельчук, І. П.; Чирка, Ю. Д. (Science-based technologies, 2009)
Maximum Likelihood Method was applied for synthesis of adaptive detection algorithm of radar pulse signals sequence reflected from a target which moves with constant speed. The  effectiveness of offered and algorithms, that is invariant to noise power, in comparison with known algorithms is investigated.